Rancang Bangun Sistem Informasi Objek Wisata di Pulau Sipora Kabupaten Kepulauan Mentawai Berbasis Webgis - Sefni Tresiawati; Dwi Arini; Anisya Anisya (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
WebGIS is a web-based Geographic Information System consisting of several interrelated components. WebGIS is a combination of graphic mapping design, digital maps with geographic analysis, computer programming, and a database that are interconnected into one part of web design and mapping web. WebGIS is a GIS application distributed in a computer network to integrate and disseminate geographic information visually on the world wide web. The objectives achieved in this study are to identify the types of tourism distribution on Sipora Island, Mentawai Islands Regency and to design and build a tourism object information system on Sipora Island, Mentawai Islands Regency based on webGIS. From the research conducted, it can be concluded that based on the survey results, there are 22 points. Waterfall tourism consists of 7 tours, cultural tourism consists of 2, beach tourism consists of 8 and marine tourism consists of 5. Where the tourism is spread across 2 sub-districts. Where in the North Sipora sub-district there are 15 points and South Sipora 7 points. Design and Build a tourism information system for Sipora Island, Mentawai Islands Regency using Quantum GIS as initial data processing. Then combined with a website that has been designed using the Visual Studio Code application.